Sequential anlotinib and camrelizumab combination therapy achieves exceptional survival in multi-driver mutated, TMB-low/PD-L1-low/MSS pulmonary sarcomatoid carcinoma: case report and literature review - Zhu, Jun; Zhu, Ai; Li, Gang; Liu, Lidong; Gao, Ziran; Liu, Jiayun; Ye, Yunfei; Zhu, Xunzhi; Li, Yi; Chen, Hong; Huang, Meijin (Frontiers in Immunology, 2026)
Pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive subtype of non-small cell lung cancer (NSCLC) whose molecular characteristics and therapeutic strategies remain poorly defined. This case report documents an exceptional 72-month overall survival in a 40-year-old male patient with stage IVa pulmonary sarcomatoid carcinoma (PSC). The patient harbored seven coexisting driver mutations [ROS1, RET(exon16,exon19), TSC2, ALK, STK11, PTEN] and exhibited triple-negative immunosuppressive biomarkers: low PD-L1 expression (TPS 3%), low tumor mutational burden (TMB, 11mut/Mb), and microsatellite stable (MSS) status. Sequential anlotinib (anti-angiogenic drug) and camrelizumab (PD-1 inhibitor) combination therapy overcame three biological barriers: (1) angiogenesis inhibition reversed PD-L1 primary resistance by remodeling the tumor microenvironment; (2) treatment induced neoantigens bypassed TMB-L/MSS limitations; (3) multi-target synergy against seven driver mutations. This approach resulted in unprecedented survival outcomes: the 72-month overall survival dramatically exceeds the median OS of less than 12 months reported for advanced PSC, and the patient maintained a progression-free survival of over 37 months on combination therapy, surpassing historical PFS benchmarks. This case provides a clinically actionable framework for managing multi-driver mutated, immunoresistant PSC.